MERGERS AND ACQUISITIONS IN TURKEY: AN ANALYSIS FROM 2012-2022 IN A TRANSFORMING ECONOMY (Third Sector Social Economic Review, 2024)
This study aims to examine the mergers and acquisitions (M&A) market in Turkey between 2012 and 2022. The research emphasizes Turkey's transformation into a global player by analyzing various parameters such as transaction volume, foreign and financial investors, and transaction sizes. The data analysis, conducted using SPSS 24.0, relies on reports on company acquisitions and mergers in Turkey between 2012 and 2022, creating a dataset for analysis. Statistical methods including frequency distributions, descriptive statistics, regression analysis, and cross-tabulation tests were employed to present the findings through tables and graphs. The results indicate an increase in the number of M&A transactions but fluctuation and decrease in transaction volume. It was observed that the significance of foreign investors increased, the influence of financial investors varied over time, and the average transaction size generally decreased. This study sheds light on the dynamics and evolution of the M&A market in Turkey over time, offering an original contribution by examining its trends and patterns.
Keywords: Mergers; Acquisitions; Strategic Management; Global Market; Financial Performance